PENGARUH KARAKTERISTIK CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN EMISI GAS RUMAH KACA - Triana Chaerun Niza; Dwi Ratmono (Diponegoro Journal of Accounting, 2019)
This study aims to examine the relation between the characteristics of corporate governance and greenhouse gas emissions disclosure. The characteristics of corporate governance that used were the proportion of female commissioners, the proportion of independent board members, the number of board members, the number of audit committee members, the frequency of audit committee meetings, and the financial competence of audit committee members. The The population are the non-financial company listed on Indonesia Stock Exchange in 2015-201. Then there were 69 samples. Multiple regression analysis is used to test the hypothesis. The results indicate that the proportion of independent board members and the frequency of audit committee meetings have a positive significant effect to greenhouse gas emissions disclosure. Whereas the proportion of female commissioners, the number of board members, the number of audit committee members, and the financial competence of audit committee members did not affect the greenhouse gas emissions disclosure.